(untitled) (Research, Society and Development, 2022)
Currently, decentralized educational management or democratic management is a reality worldwide and in Brazil. As the democratic process develops, education needs to accompany society, forming citizens capable of exercising democracy as they wish. Theoretically, Brazilian schools have democratic management, however, in practice, implementation has still taken place for decades and faces several challenges from different factors, both internal and external. The present study is justified by the need to point out these challenges, with the objective of briefly analyzing the challenges and pointing out possible solutions. To this end, a qualitative research was used, in relation to the objectives, it is an exploratory research and the procedures, the study was characterized as bibliographic. The research was carried out in a virtual environment, in reliable databases, with published scientific articles and also includes virtual environments for studies and research in Pedagogy for theoretical reference. An analytical reading was carried out and the main aspects were highlighted. Afterwards, the textual production was elaborated in two titles that are correlated: School management and democratic management and Challenges faced in democratic school management. The author’s impressions as well as the conclusions make up the Final Considerations.